Anabolic steroids in the UK: an increasing issue for public health. (4th May 2017) - McVeigh, Jim; Begley, Emma
Abstract: Aim : The aim of the paper was to identify changes in the extent and patterns of anabolic steroid use in the United Kingdom to better understand the public health implications within the context of the current health-related evidence base. Methods : Using the two time points between 1995 (prior to legislation changes in the United Kingdom) and 2015, a review of the evidence related to health harms was conducted, in conjunction with needle and syringe programme (NSP) data in Cheshire & Merseyside (UK) relating to anabolic steroid users. Findings : Dramatic increase in the number of anabolic steroid users accessing NSPs, 553 in 1995 to 2446 in 2015, now accounting for 54.9% of clients. With the inclusion of pharmacy NSPs, this rose to 5336 individual anabolic steroid users. Conclusions : Key changes in our knowledge during the 20 years, in particular, in relation to HIV prevalence, changes in the market and patterns of use make anabolic steroid use a public health concern. In the context of increasing numbers of injectors, there is a need for comprehensive interventions.